Wicca e corporeidade: "a bruxaria moderna e o imaginário do corpo" - Alves, Ana Carolina Chizzolini (2011)
The aim of the present research is to examine the relations established between corporeality and Wicca the modern witchcraft. Such relations can be explored due to a new imaginary of the body, originated from the western society history, with the advent of Modernity, and still developed nowadays. This new imaginary goes a long way toward new religious movements known as The New Age. The so-called New Age represents a sort of fertile ground upon which new religions, from a tradition-based perspective, have steadily strengthened and established in the western part of the world, combining oriental symbols, mixing beliefs freely and promoting creativity among their followers. This is the case of Wicca, which is presented as old witchcraft merging into everyday urban elements. Wicca is closely related to a religion of corporeality because, in the same way as a New Age moviment, the body is viewed as the core of practice, and a means of social transformation Wicca aims at. Ecological, psychological and corporeal transformation, making its followers´ bodies a magical extension of nature